2004
DOI: 10.1093/bja/aeh253
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in intravenous anaesthesia

Abstract: Efforts to develop new hypnotic compounds continue, although several have recently failed in development. Propofol has been reformulated in various presentations with and without preservatives. Pharmacokinetic and pharmacodynamic differences exist between some of these preparations, and it is currently unclear whether any have substantial advantages over the original presentation. The use of target-controlled infusion (TCI) has been extended to include paediatric anaesthesia and sedation. Application of TCI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 130 publications
1
49
0
2
Order By: Relevance
“…In this study many confounding factors associated with propofol injection pain, including the temperature of the solution, the size of the vein and speed of injection, were controlled between the groups by using veins of similar size on the hand, 0.5 ml/s injection rate and propofol at room temperature. [12][13][14] Observed intragroup gender pain perception differences, revealed that female patients had statistically significant greater pain perception than men within both groups, supports the observation of Fillingim [3] that women show greater perceptual responses than men to mechanical pain, ischaemic pain and cold pressor pain. Sex differences in experimental pain perception using a wide variety of stimuli have been widely reported; with female typically displaying greater pain sensitivity than male, but the mechanism underlying these differences remain unclear.…”
Section: Discussionsupporting
confidence: 71%
“…In this study many confounding factors associated with propofol injection pain, including the temperature of the solution, the size of the vein and speed of injection, were controlled between the groups by using veins of similar size on the hand, 0.5 ml/s injection rate and propofol at room temperature. [12][13][14] Observed intragroup gender pain perception differences, revealed that female patients had statistically significant greater pain perception than men within both groups, supports the observation of Fillingim [3] that women show greater perceptual responses than men to mechanical pain, ischaemic pain and cold pressor pain. Sex differences in experimental pain perception using a wide variety of stimuli have been widely reported; with female typically displaying greater pain sensitivity than male, but the mechanism underlying these differences remain unclear.…”
Section: Discussionsupporting
confidence: 71%
“…TIVA, performed with IV drugs which have more rapid onset and shorter recovery profiles, is available. Among these iv drugs, propofol is the most commonly used iv anesthetic agent to produce adequate pain control [21], and it is commonly administered with an opioid such as remifentanil [22]. Many known benefits of TIVA include reduced postoperative pain, less postoperative nausea and vomiting, and, most interestingly, less risk of organ toxicity such as hepatic toxicities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Many known benefits of TIVA include reduced postoperative pain, less postoperative nausea and vomiting, and, most interestingly, less risk of organ toxicity such as hepatic toxicities [23]. Recently, TIVA has been widely used during various types of surgical procedures [22]. However, the influence of IV anesthetics on hepatic functions is not well established; therefore, it was our goal to determine the effects of TIVA with propofol-remifentanil or propofol-fentanyl on postoperative hepatic functions and to compare their relative safety.…”
Section: Discussionmentioning
confidence: 99%
“…Derived from alkylphenol, its action is fast and smooth, and it is classified as a shortacting, rapidly metabolized drug (SNEYD, 2004;DUKE, 1995). Due to its phenolic composition, glucuronidation is the main metabolic pathway of its inactivation, which occurs through catalysis of UDP-glucuronyltransferase (UGT) 1.6 isoenzyme (COURT; GREENBLATT, 2000).…”
Section: Introductionmentioning
confidence: 99%